Progress on Respiratory Syncytial Virus Vaccine Development and Evaluation Methods - Lie Deng; Hongjie Cao; Guichang Li; Kaiwen Zhou; Zihan Fu; Jiaying Zhong; Zhongfang Wang; Xiaoyun Yang (Vaccines)
Respiratory syncytial virus (RSV) remains a significant global health threat, especially to infants, the elderly, and immunocompromised individuals. This review comprehensively explores the progress in RSV vaccine development, the immune evaluation methods, and immunological surrogate. The RSV fusion (F) protein, a primary target for vaccine development, has been engineered in prefusion conformation to elicit potent neutralizing antibodies, while the attachment (G) glycoprotein and other immunogens are also being explored to broaden immune responses. Advances in diverse vaccine platforms, ranging from live attenuated and protein subunit vaccines to cutting-edge mRNA- and nanoparticle-based formulations, highlight the field’s progress, yet challenges in balancing safety, immunogenicity, and durability persist. Central to these efforts is the identification and validation of immunological surrogates, which may serve as critical benchmarks for vaccine efficacy. Neutralizing antibody titers, multifunctional T cell responses, and B cell memory have emerged as key correlates of protection. However, the feasibility of these surrogates depends on their ability to predict clinical outcomes across diverse populations and settings. While neutralizing antibodies block the virus directly, T cell responses are essential for clearing infected cells and preventing severe disease, and B cell memory ensures long-term immunity. Integrating these immunological markers into a cohesive framework requires standardized assays, robust clinical validation, and an in-depth understanding of RSV-induced immune response.